Pengaruh Komunikasi, Motivasi dan Lingkungan Kerja terhadap Kinerja Karyawan Pada PT. Nutrifood Medan - Pita karni Zendrato; Latersia br gurusinga (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2022)
Employee performance is very dependent on the input generated by the employee and the output unit produced by the employee. The purpose of this study was to determine and analyze communication, motivation and work environment influence on performance partially and simultaneously. The research used is research with quantitative methods. The technique of collecting data in this study was done by distributing questionnaires. The data analysis technique in this study used the classical assumption test, multiple regression, hypothesis testing with SPSS 22 software. The population in this study was 83 employees at PT. Nutrifood Medan. Based on the results of this study, the significance value of communication on performance based on the t test was obtained for tcount > ttable (3.857 > 2.001). thus the conclusion: communication has a positive and significant effect on performance. Based on the results of this study, the significance value of motivation based on the t-test was obtained at tcount > ttable (4.912 > 2.001). thus the conclusion: motivation has a positive and significant effect on employee performance. based on the t test, it was obtained that tcount > ttable (2,661 > 2,001). thus H1 is accepted. the conclusion: the work environment has a positive and significant effect on employee performance at PT. Nutrifood Medan. based on the results of the F test above, the value of Fcount > Ftable is (25,636 > 3.16) (Sig. 0.000 < 0.05), thus the conclusion: communication, employee placement and work environment have a positive and significant impact on employee performance